(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to highlight the role of educational inspection in promoting the concept of green education within educational institutions in Libya as one of the modern approaches supporting the achievement of sustainable development. The study adopted the descriptive-analytical approach, through analyzing the current status of educational practices related to green education and examining the role of educational inspectors in supporting and enhancing these practices. The findings revealed a need to strengthen the awareness of educational staff regarding the concept of green education, while emphasizing the importance of activating the role of educational inspection through guidance, monitoring, training, and continuous professional support. The study concludes that educational inspection can serve as a strategic mechanism for integrating environmental sustainability principles into educational processes and fostering a culture of green education within Libyan educational institutions.